Hazard and seismic reinforcement analysis for typical large dams following the Wenchuan earthquake - Lin, Peng; Huang, Bo; Li, Qingbin; Wang, Renkun (Engineering geology, 2015)
The primary aim of this research is to analyze the hazards and seismic performance of reservoirs and typical large dams based on a field investigation following the Wenchuan 8.0 earthquake. The current seismic performance standards being achieved are discussed and further suggestions are given for super high dams. Based on field investigations, statistics are also given on damaged small reservoirs and damage severities, due to the many various types of earthquake threat. It is of interest to note that the major structures of the medium-sized hydropower stations on the Minjiang river did withstand the Wenchuan earthquake, despite earthquake intensity exceeding engineering design expectations. All the dams remained overall stable. The Shapai roller-compacted concrete (RCC) arch dam and the Zipingpu concrete-faced rockfill (CFR) dam suffered damage. The main earthquake-induced hazards to the dam structures and to both abutments are detailed. Case study analyses of the hazards and reinforcement provision revealed that: 1) The Wenchuan earthquake proved very dangerous for small reservoirs, with destroyed reservoirs widely distributed. The risk of failure of small dams can be classified into three levels based on field investigation. 2) The damage to and behavior of the large dams in the area affected by the earthquake prove that the Chinese codes relating to the seismic design of large dams are appropriate. 3) Appropriate reinforcement can increase the overall stiffness of abutments, riverbed foundation and the adjacent slopes, further improving the seismic performance of dams. 4) The design and management of emergency responses, to cope with extreme conditions, should be improved, and a unified response platform, covering all hydropower engineering projects in each valley should be established. The effects to be expected and the seismic design measures to be taken still pose great challenges for engineers in respect of large dams. •Distribution of damaged reservoirs and damage severities was given.•Stable reasons of typical large dams were analyzed.•Appropriate reinforcement improves high dam overall seismic performance.•Chinese seismic design codes for high dams are appropriate.